The relationship between individual differences and Spanish achievement among Chinese undergraduate students - Lu, Qi; Fernández Sánchez, Eulalio (Frontiers in Psychology, 2025)
This study investigates how three individual differences (language anxiety, Expectancy–Value Motivation, and social identity) predict academic performance in Spanish as a foreign language among a sample of 317 Chinese undergraduate students majoring in Hispanic Philology. A designed questionnaire was used to collect all the data from the participants. The results demonstrated that while Chinese learners of Spanish generally possess a high level of value motivation, especially utility value, they showcase a medium level of expectancy. Additionally, participants show a medium-low level of language anxiety in the institutional context of Spanish as a foreign language (ELE) and experience a positive trend towards changes in their social identity, particularly when it comes to self-confidence. Moreover, achievement value and self-confidence emerge as positive predictors of Spanish achievement, while language anxiety is the only negative predictor. Based on the above, limitations and future lines of research are also discussed.